Pobres, pobreza e cidadania: Os desafios recentes da proteç\~ao social - Luciana Jaccoud (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– This paper analyzes the recent trajectory of social security in Brazil from the evolution of the contributive and no contributive income guarantee programs. The Brazilian social protection has gone through important changes in recent years, on the one hand, as an answer to the configuration given by the Federal Constitution to social security and social assistance policies and, on the other hand, to the emergence of cash transfer programs to the extremely poor. The goal is to analyze these changes and its impacts, calling attention to the movement of gradual inclusion of new groups of beneficiaries, to extended coverage of a diversity of risk situations and their participation in the labor market. However, it also emphasizes the incomplete characteristics of this process, which is followed by new tensions, such as the context of precarious configuration of the labor market and the difficulties in guaranteeing the coordination between the anti-poverty policies and the consolidation of the social security.
Keywords: I38; 330